Rekonsiliasi Epistemologi Antara Agama dengan Sains (Telaah tentang Pemikiran Filsafat Seyyed Hossein Nasr) - Maksum, Ali (ULUL ALBAB Jurnal Studi Islam, 2001)
The framework of thinking about modern scholarship tries to break away from the spiritual dimension. Human consciousness is herded towards the secular. As a result, modern Western humans no longer know about the meaning and purpose of life. Then revisions arose in the form of relativizing the absurdities that had been attributed to the scientific method, while at the same time trying to pave the way for the entry of divine values and spiritual dimensions into the basis of scientific epistemology, ontology and axiology. Some even see that value based on revelation (religion) can enter the scientific methodology process. The scientific method can no longer be maintained in a neutral sense in the absolute sense. Postmodern criticism does not eliminate rationality and does not divert human attention from material phenomena to the spiritual world, but complements rationality with philosophical keys that contain world views and religious morality. Nasr's epistemological thinking has significance with modern or postmodern human consciousness, which requires moral awareness and the meaning of life. Nasr offers in the form of religious-spirituality formulations within the framework of modern human thought.